Physoschistura longibulla, a new loach (Cypriniformes: Nemacheilidae) from Irrawaddy basin in central Myanmar - Lin, Feng; Liu, Shuwei; Zaw, Paing; Qin, Tao; Chen, Xiaoyong (Zootaxa, 2024)
Physoschistura longibulla, a new species and the first species of the revised genus Physoschistura from Pyin Oo Lwin of Irrawaddy basin, can be distinguished from other congeners by the combination of following characters: posterior chamber of air bladder well developed, connecting anterior with a long and thin tube, long and oval; dorsal fin with 81/2 branched rays, its origin slightly anterior to pelvic-fin base vertically; lateral line complete and straight, with 93–102 pores; pectoral fin with 8–9 branched rays, reaching 1/2 to 2/3 of distance to pelvic-fin base; suborbital flap absent in male; axillary pelvic lobe present; caudal fin with 9 + 8 branched rays.